Masyarakat Tani Masa Depan: Perbenturan Budaya Lokal Dan Global - Darmawan Salman; Sitti Bulkis; Arifin Sallatang (Jurnal Dinamika Sosial Ekonomi, 2001)
A number of external and internal phenomena indicate that how weak the position of our agriculture in facing the globalization in the same time, wich far away the extent of the paesant’s local culture can be stood on the clash of capitalism global culture, becoming a question. In this respect, there are two forms of cultural clash that can be occurred, those are cultural hybridization and cultural underdevelopment. Ideally, the peasant community in the future is a result of the "cultural hybridization, a marriage between native local culture element and outside global culture element, so that it is going on a so called globalisation. This direction will be attained when the peasant has a powerness social-economically, because by the social economically powerness it is the local cultural element possesses a power or strength to marry with the global culture.Keywords: peasant community, local and global cultures, cultural hybridization.